NILAI-NILAI MULTIKULTURAL MELALUI PERMAINAN TRADISIONAL UNTUK KELOMPOK B DI RA NAHDLATUSY SYUBBAN GONDANGLEGI-MALANG - Sugiarti, Rika Dwi; Rohmawati , Afifatu (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
The development of multicultural values through traditional games has a major influence on early childhood at RA Nahdlatusy Syubban. The research objective is to instill multicultural values through traditional games including dhakon, bekel ball, rope jumping, and suweng cubek-cubek. The research method used is qualitative-descriptive research, using observation data/field notes, interviews, and documentation. The findings of the data obtained in research activities include multicultural learning based on the values of tolerance, mutual respect, democracy, mutual love, and togetherness in unifying the goals of the game. Traditional games can develop their own culture, revive local wisdom, and can be carried out independently. together. The results of this study in the development of multicultural values include the values of tolerance, democracy, justice, mutual trust, and togetherness. Research suggestions emphasize the cultivation of multicultural values in children not only on traditional game concepts. However, in learning activities that can build a pattern of habituation, the growth of children to adulthood will naturally instill multicultural values in their next life.